2022
DOI: 10.1007/s10803-022-05733-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Art Appreciation in Autism: A Measure of Reduced Intuitive Processing

Abstract: Art appreciation reflects an initial emotional and intuitive response to artwork evaluation, although this intuitive evaluation can be attenuated by subsequent deliberation. The Dual Process Theory of Autism proposes that individuals with Autism Spectrum Disorder (ASD) have a greater propensity to deliberate and reduced intuition compared to matched controls. Evaluations of high- and low-quality artworks were undertaken by 107 individuals with a diagnosis of ASD and 145 controls. Controls consistently evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
4
3
0
Order By: Relevance
“…Future research can explore whether individuals on the autism spectrum produce logically accurate responses more rapidly and effortlessly than non-autistic individuals. Combined with the present findings of a bias away from intuitive responses and towards deliberative responses in this study (see also Brosnan & Ashwin, 2022;Brosnan et al, 2016Brosnan et al, , 2017, future research can explore the possibility of autism being characterised by rapid, effortless 'non-social' processing and slow, deliberative 'social' processing (opposite to the neurotypical pattern).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Future research can explore whether individuals on the autism spectrum produce logically accurate responses more rapidly and effortlessly than non-autistic individuals. Combined with the present findings of a bias away from intuitive responses and towards deliberative responses in this study (see also Brosnan & Ashwin, 2022;Brosnan et al, 2016Brosnan et al, , 2017, future research can explore the possibility of autism being characterised by rapid, effortless 'non-social' processing and slow, deliberative 'social' processing (opposite to the neurotypical pattern).…”
Section: Discussionsupporting
confidence: 69%
“…Autism spectrum disorder (ASD) is characterised by differences in social communication and interaction as well as patterns of restricted and repetitive behaviours, interests and activities, and is diagnosed in around four times as many males as females ( American Psychiatric Association [APA], 2013 ; World Health Organization [WHO], 2018 ). The Dual Process Theory of Autism ( Ashwin & Brosnan, 2019 ; Brosnan & Ashwin, 2022 ; Brosnan et al, 2016 , 2017 ; Lewton et al, 2019 ) proposes that autistic individuals and those high in autistic traits engage in deliberative processing to a greater degree and intuitive processing to a lesser degree than neurotypical peers. From this view, deliberation and reduced intuition in decision-making by autistic individuals can be characterised as a disruption to the default-interventionist position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderately sized (albeit non-significant) effect of autistic adults’ trend towards slower SLT lie speeds may reflect enhanced deliberative processing relative to intuitive processing. This would be consistent with the Dual Process Theory of Autism ( Ashwin & Brosnan, 2019 ; Brosnan & Ashwin, 2022 , 2023 ; Brosnan et al, 2017 , 2016 ); Such non-neurotypical strategies have been suggested to underpin deception inclination and ability in autistic children ( Ma et al, 2019 ) and adults ( van Tiel et al, 2021 ). The higher cognitive cost of deliberative strategies may mean that some autistic individuals are less inclined to engage in such strategies and therefore appear less socially motivated ( Livingston et al, 2019a ).…”
Section: Discussionsupporting
confidence: 82%
“…A strength in rule-governed processing has been proposed to characterize autism. Theoretical accounts of deliberative analytical thinking strengths in autism, such as the Dual Process Theory of Autism ( Brosnan et al, 2016 , 2017 ; Lewton et al, 2019 ; Ashwin and Brosnan, 2020 ; Brosnan and Ashwin, 2022a , b ), may also be a potential framework for understanding the mechanisms underpinning social stories. The Dual Process Theory of Autism proposes an autistic preference for slower, explicit, deliberative, analytical processing (compared with a non-autistic preference for rapid, implicit, intuitive processing).…”
Section: Social Stories™mentioning
confidence: 99%